Volatile oil constituents of Lemon grass (Cymbopogon citratus Stapf) cultivated in north of IRAN - D Yazdani; Sh Rezazadeh; NA Shahabi (Institue of Medicinal Plants, ACECR, 2004)
The genus Cymbopogon, a one of Poaceae family, is widely cultivated in tropical and subtropical regions.‏The essential oils extracted from this genus used in food, soap, perfumary and other related industries. The C. citratus stapf species was cultivated for first time in the north of Iran. Therefor, recognition of essential oil composition is necessary. Essentiol oil extracted with hydrodistillation method from fresh leaves, and analysed by GC/MS. From 91.1% of identifed components, Citral (49.43%), Citronellal (20.25%) and Geranyl acetate (6.41%) were major components respectively.